2020
DOI: 10.1371/journal.pone.0236728
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychiatric symptoms before the diagnosis of Parkinson’s disease in a nationwide cohort: A comparison to patients with cerebral infarction

Abstract: Objectives Psychiatric symptoms (PS) can be non-motor features in Parkinson's disease (PD) which are common even in the prodromal, untreated phase of the disease. Some PS, especially depression and anxiety recently became known predictive markers for PD. Our objective was to explore retrospectively the prevalence of PS before the diagnosis of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Once pontine structures (including the magnocellularis and subcoeruleus nuclei) are sufficiently dysfunctional, isolated REM sleep behavior disorder (iRBD) appears [64]. Involvement of other brainstem nuclei may give rise to prodromal neuropsychiatric symptoms including anxiety and mood disorders [65,66]. Supporting this, a recent study reported that depression and anxiety were more prevalent in iRBD patients compared with a group of unselected de novo PD patients [67].…”
Section: Utility Of the Soc Modelmentioning
confidence: 99%
“…Once pontine structures (including the magnocellularis and subcoeruleus nuclei) are sufficiently dysfunctional, isolated REM sleep behavior disorder (iRBD) appears [64]. Involvement of other brainstem nuclei may give rise to prodromal neuropsychiatric symptoms including anxiety and mood disorders [65,66]. Supporting this, a recent study reported that depression and anxiety were more prevalent in iRBD patients compared with a group of unselected de novo PD patients [67].…”
Section: Utility Of the Soc Modelmentioning
confidence: 99%
“…The imperative role of mental health professionals has been highlighted in terms of addressing the negative health beliefs and to reduce the overall stigma associated with mental disorders. 12,[20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, such symptoms can be reactive to the diagnosis of the CNS disorder itself [ 10 , 11 , 12 ], while in other cases they are reported as possible consequences of pharmacological treatments [ 13 , 14 ]. In addition, the same pathophysiological pathways underlying neurological manifestations can contribute to the development of psychopathological features in CNS disorders, strongly suggesting a neurobiological link between neurological and psychiatric symptoms [ 9 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%